Analysis of Raw Material Planning Using the EOQ (Economic Order Quantity) Method (Case Study on MSMEs Martabak Binaria) - Romansyah Sahabuddin; Dila Suryani; Nurhikmah Maharani; Nurfitriani Azizah M; Anandha Amelia (Universitas Muhammadiyah Palu, 2024)
The study analyzes the method of Economic Order Quantity (EOQ) and Reorder Point (ROP) at Martabak Binaria MSMEs in an effort to improve efficiency in raw material inventory management. Based on sales forecasting and cost comparisons, the study found that the use of EOQ resulted in better cost control compared to previous approaches by companies. In addition, ROP ensures raw material orders are placed on time, avoiding disruptions in the production process. These findings underscore the importance of efficient inventory planning in supporting MSME operations, potentially increasing efficiency, reducing costs, and strengthening their competitiveness in the market. Based on the results of the analysis, it is known that in 2023 Martabak Binaria can generate a sales volume of 999,936,000 and purchase raw materials for production based on the most economical ordering method for each production activity, namely by using the economical ordering amount method or EOQ.